Extreme Identities: An examination of extreme sports and the creation of identity within the extreme sports experience - Patch, Sophie (Centre for Film and Media Studies, 2020)
In recent years has been a rapidly growing increase in the popularity of extreme sports. Whilst the root of the exact reasons that extreme sports have grown so dras;cally as an industry is not en;rely clear, there are many theories and sugges;ons which can create a narra;ve to the evolu;on of the sports. Not only have the sports become more popular, but the varie;es of the sports and the varie;es of the par;cipants have also increased, crea;ng more diversity and the evolu;on of a extreme sports culture. This has coincided, inten;onally or un-inten;onally, with the glamorisa;on and commodifica;on of extreme sports lifestyles and the technological advancements of the twenty-first century. In line with the above, the purpose of this study, and the photographic project which accompanies it, is to examine; • What are the factors that contribute to the popularity of extreme sports • Who takes part in extreme sports • Why do people take part • What is the future for extreme sports and it’s par;cipants The photographic project comprises of four photographs of each par;cipants, two of which are portraits and two of which are supplied by the par;cipants themselves. The inten;on of the photographs is to give insight into both who the par;cipants are as individuals and as athletes and how they view themselves within these roles. Interviews were also conducted alongside which are referenced throughout the paper. The paper combines the research and theories of other scholars, against the findings of my own study and how the photographic project represents this, to try and draw answers to the above state ques;ons. The results were varied and did not offer full answers but rather sugges;ons into where more research could be done to further this study and future studies. Most notably; Extreme sports and femininity, Extreme sports and diversity, Extreme sports and classism and Extreme sports and environmentalism.